A Sensitive SPE-ECD-GLC Procedure for Analyzing Simazine Quantitatively in Food Products - Anil Kumar; Naisergik Deepika Khanna (International Journal of Biochemistry and Biomolecule Research, 2025)
Short and simple solid-phase extraction (SPE) method interfacing and hyphenating gas liquid chromatographic-electron capture detection (GLC-ECD) method has been developed for the qualification and quantification of simazine in some daily used agro products. United States Pharmacopeia G-42 gas chromatography stationary phase with ZB-35a, HTb Inferno-cZ (Zebron, Za) capillary column with an enlarged and extended temperature range of –60° to 400°C and electron capture detector was selected correlating some chemical, physical and structural features of Simazine. Attempted the higher temperature range which was programmed with 20–25 minutes having 0.94 ml/min of gas flow showing theoretical plates (~106) and optimum resolution (Rs ~ 2.04 min) with a limit of detection and limit of quantification values of 0.0013 μg/L and 0.13 μg/L, respectively. Accurate LOQ was achieved by using this method and is almost below the maximum residue concentrations recommended by the Indian Pharmacopeia Standards. Recoveries of the simazine obtained from agricultural samples by spiking ranged from 79.77 to 99.60% with relative standard deviations far below 3.17 %. More than five minutes of SPE residual workup makes the proposed method simple and fast having good economic importance for the quantitative analysis of simazine in common environmental institutes, medical colleges, and civil hospitals serving society.
Keywords: GLC-ECD; LOD; LOQ; Simazine; residues